1971
DOI: 10.1159/000179902
|View full text |Cite
|
Sign up to set email alerts
|

Possibility that Angiotensin Resulting from Unilateral Kidney Disease Affects Contralateral Renal Function

Abstract: Evidence from previous theoretical and experimental studies has indicated that angiotensin formed as a result of unilateral kidney disease will not produce chronic hypertension unless there is also a sodium and fluid retaining effect on the otherwise normal contralateral kidney. Therefore, the present experiments were conducted in dogs to determine whether or not blood angiotensin concentrations similar to those found in patients with unilateral kidney disease can cause significant water and salt retention by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Endothelin-1 (-log M) Figure 2 Concentration-response curves to extraluminal endothelin-1 in mesenteric resistance arteries with (0) and without endothelium (0) rats and similar to the relaxation induced by intraluminal acetylcholine (Table 1).…”
Section: Drugsmentioning
confidence: 70%
See 1 more Smart Citation
“…Endothelin-1 (-log M) Figure 2 Concentration-response curves to extraluminal endothelin-1 in mesenteric resistance arteries with (0) and without endothelium (0) rats and similar to the relaxation induced by intraluminal acetylcholine (Table 1).…”
Section: Drugsmentioning
confidence: 70%
“…This could occur due to greater vascular endothelin production or pressure per se. Angiotensin II, which is elevated in renovascular hypertension (Brunner et al, 1962;Fourcade et al, 1971;Ploth et al, 1977;Huang et al, 1981;Miyazaki et al, 1986), is known to stimulate the production of endothelin 6 5 4…”
Section: Discussionmentioning
confidence: 99%
“…11 As mentioned, earlier studies have suggested the existence of altered tubular function and hemodynamics in the kidney contralateral to the stenotic kidney.…”
Section: Figure 8 Contralateral Kidneys Of Goldblalt Hypertensive Ramentioning
confidence: 91%
“…It has been suggested that increased activity of the renin-angiotensin system resulting from clipping of one renal artery would be expected to influence the VOL 3, No 3, MAY-JUNE 1981 nonclipped kidney. 11 This has received support from studies demonstrating that administration of angiotensin antagonists reduce the elevated renal vascular resistance in the contralateral kidney; 11 - 13 however, there is little information regarding the individual GFR and excretory responses of the clipped and nonclipped kidneys to blockade of the renin-angiotensin system. Of interest is the unique circumstance occurring in this hypertensive model of a renin-depleted kidney existing in an environment of elevated plasma renin levels.…”
mentioning
confidence: 99%
“…However, in the dogs that received angiotensin, the calculated circulating angiotensin remained almost exactly constant except for a slight elevation at the lowest rate of sodium output. If angiotensin shifts the pressure-sodium output curve to the right (a finding previously shown in acute studies on dogs by Fourcade et al 32 ), one would expect the points on the lower portion of the "normal" curve to have been displaced to the right by the excess angiotensin, and the points on the upper portion of the curve to have been displaced to the left by lack of angiotensin. Thus, the "normal" curve would have been markedly steepened in comparison with the "angiotensin" curve.…”
mentioning
confidence: 82%